2008
DOI: 10.1016/j.physc.2007.08.021
|View full text |Cite
|
Sign up to set email alerts
|

An inhomogeneous Josephson phase in thin-film and high-Tc superconductors

Abstract: In many cases inhomogeneities are known to exist near the metal (or superconductor)-insulator transition, as follows from well-known domain-wall arguments. If the conducting regions are large enough (i.e. when the T = 0 superconducting gap is much larger than the single-electron level spacing), and if they have superconducting correlations, it becomes energetically favorable for the system to go into a Josephson-coupled zero-resistance state before (i.e. at higher resistance than) becoming a "real" metal. We s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 42 publications
(54 reference statements)
1
37
0
Order By: Relevance
“…3), one then could have concluded that even in the insulating phase where T c = 0, the average superconducting gap still survives. Thus the observed trend of the faster decay in T c than in ∆, together with the inhomogeneous state, offers a strong support to hypothesis that the so-called "homogeneously disordered "superconducting films near SIT [1,2,8,15] can in fact be viewed as granular-like superconducting structure or Josephson phase suggested by Imry et al [3]. This, in its turn, implies that the bosonic mechanism of the superconductorto-insulator transition [29] becomes relevant.…”
Section: Shown Insupporting
confidence: 78%
See 1 more Smart Citation
“…3), one then could have concluded that even in the insulating phase where T c = 0, the average superconducting gap still survives. Thus the observed trend of the faster decay in T c than in ∆, together with the inhomogeneous state, offers a strong support to hypothesis that the so-called "homogeneously disordered "superconducting films near SIT [1,2,8,15] can in fact be viewed as granular-like superconducting structure or Josephson phase suggested by Imry et al [3]. This, in its turn, implies that the bosonic mechanism of the superconductorto-insulator transition [29] becomes relevant.…”
Section: Shown Insupporting
confidence: 78%
“…Upon increasing disorder, we observe suppression of the superconducting critical temperature Tc towards zero, enhancement of spatial fluctuations in ∆, and growth of the ∆/Tc ratio. These findings suggest that local superconductivity survives across the disorder-driven superconductor-insulator transition.PACS numbers: 74.50.+r, 74.78.Db, A pioneering idea that in the critical region of the superconductor-insulator transition (SIT) the disorderinduced inhomogeneous spatial structure of isolated superconducting droplets develops [1,2], grew into a new paradigm [3]. Extensive experimental research of critically disordered superconducting films revealed a wealth of unusual and striking phenomena, including nonmonotonic temperature and magnetic field dependence of the resistance [2,4,5,6], activated behavior of resistivity in the insulating state [1,5,6,7,8], nonmonotonic magnetic field dependence of the activation temperature, and the voltage threshold behavior [8,9,10].…”
mentioning
confidence: 99%
“…Below T c a weak superconducting response is observed allowing the superfluid density ρ s0 to be estimated. This material is observed to fall on the general scaling line for the cuprate superconductors, ρ s0 /8 ≃ 4.4σ dc T c [19], but in a region typically associated with the c-axis response where the superconducting response is due to Josephson coupling, suggesting that this material is indeed phase separated and constitutes a Josephson phase [20].…”
mentioning
confidence: 91%
“…However, as the electronic doping is increased the material becomes more homogeneous, the size of the superconducting regions increases and the "granularity" is reduced, allowing the system to revert to a more conventional behavior. It should be noted that in this "large-grain" picture, the Uemura relation is expected to be recovered, 37 suggesting that this is a reasonable description of the moderately-underdoped region.…”
Section: Fig 2: (Color Online)mentioning
confidence: 83%
“…35 We speculate that the severely-underdoped materials are electronically segregated into superconducting hole-rich regions, and holepoor regions that form a poorly-conducting barrier region. If the "granularity" of such a system is fine enough, then the superconducting regions will be linked through the Josephson effect, 36 in essence forming a Josephson phase, 37 and in fact it has recently been demonstrated that the scaling relation observed here can be derived for a two-dimensional Josephson array. 38 Within this framework the doping level may in principle be reduced to such an extent that Josephson coupling between the superconducting regions is no longer possible.…”
Section: Fig 2: (Color Online)mentioning
confidence: 85%